Development of Islamic Character Education Teaching Materials for Prisoners - Muhammad Akbar; Asra, Muhammad (Mimbar Ilmu, 2025)
The limitation of teaching materials in character development based on Islamic values for inmates has resulted in religious learning that does not fully address the moral, spiritual, and emotional aspects essential for rehabilitation. This study aims to develop and examine the effectiveness of an Islamic Education based textbook to strengthen the Islamic character formation of inmates. The research employed a Research and Development (R&D) approach, using the Borg & Gall model as the development framework and the Dick & Carey model for systematic instructional design. The development process included preliminary study, planning, initial product development, limited trials, and product refinement. Validation instruments were applied to assess content, language, and visual design, while data were analyzed using descriptive statistics (mean scores) and qualitative data reduction from observations and interviews. Validation results showed high average scores from material experts (3.52), instructional design experts (3.56), and language experts (3.66), indicating the product’s feasibility. Limited trials yielded a practicality score of 3.46, suggesting that the textbook is user-friendly and relevant to the needs of rehabilitation. The developed material encompassed eight main themes repentance, self-control, self-reflection (muhasabah), and spiritual relationship proven to reinforce inmates’ Islamic character. The findings confirm that textbooks based on religious values can serve as both educational and reflective media in inmate development and are recommended for replication in similar contexts to strengthen character-based education practices.